Variação do momento de transição eletrônico do sistema A1 Sigma + - X1 Sigma + da molécula NaLi. - Miranda, Bárbara Kelly Cunha de (2007)
The aim of this work is to calculate the variation of the transition moment as a function of the internuclear distance, assuming electric dipolar transitions between the eletronic states A1 Sigma + - X1 Sigma + of the NaLi molecule and by using experimental intensities. The experimental data of rovibrational transitions among these electronic states were obtained by using laser induced fluorescence technique, combined with the Fourier Transform Spectroscopy in Laboratoire Aimé Cotton in Orsay, France. The potential energy curves for both electronic levels were determined by using a method developed by Rydberg-Klein-Rees, named RKR procedure, with the spectroscopic constant obtained by Fellows. The variation of dipolar electronic transition moment as a function of internuclear distance was obtained by the use of r-centroid aproximation, and by the direct solution of the equations using the Singular Value Decomposition (SVD) methid. We also determined the Franck-Condon factor and verifield that it does not predict the experimental intensities distribution as a function of the vibrational levels in the transition. This proves that the dipolar electronic transition moment varies with the internuclear distance. It was also performed the comparison between the transition moment obtained in this work and the theoretical calculations performed by prof. F. V. Prudence and his group using the perturbation method MCQDPT of second order, where the molecular orbitals were obtained by the previous SA-CASSCF calculations. This comparison shows disagreement between the theoretical results and those obtained by the use of the experimental intensities. Probably this lack of agreement is due to the fact that the upper electronic state A1 Sigma + is strongly perturbed, as discussed in precedent works.